LENVATINIB IN TREATMENT OF RADIOACTIVE IODINE-REFRACTORY WELL-DIFFERENTIATED THYROID CARCINOMA - I. S. Romanov; A. M. Mudunov; P. A. Isaev; Yu. M. Bychkov; M. B. Dolgushin; A. A. Odzharova; L. F. Romanova (Опухоли головы и шеи)
Well-differentiated thyroid carcinoma (WDTC) comprises > 90 % of all cases of thyroid cancer. In 10–15 % of patients, distant metastases are detected which significantly worsen the prognosis. Radioactive iodine therapy remains the main type of treatment of this patient group, but for patients with so-called radioactive iodine-refractory WDTC the prognosis is very poor. After successful phase III  studies, several drugs from the group of multikinase inhibitors are being used in clinical practice for treatment of radioactive iodine-refractory WDTC, for example lenvatinib. In this article, we present a group of patients with radioactive iodine-refractory WDTC who received lenvatinib therapy.